Crescimento e sobrevivência de Escherichia coli em água cinza visando o reuso - Nunes, Kezya Cristina Frizzera (2019)
Gray water is defined as wastewater produced in showers, bathtubs, sinks, washing machines, sinks and tanks. Pathogens in gray water occur in less quantity than in domestic wastewater. However, gray water may have a high load of easily degradable organic compounds, which may favor the growth of enteric bacteria, such as fecal contamination indicators. The survival of fecal bacteria in aquatic environments depends on their ability to tolerate a number of biological stresses among them the availability of nutrients such as phosphorus and nitrogen being these nutrients biologically necessary for the survival of bacteria, such as Escherichia coli. The present work aims to evaluate the growth/survival of Escherichia coli in samples of gray water destined for reuse. The influence of nutrients (phosphorus, nitrogen and glucose) on the growth/survival of Escherichia coli in gray water was evaluated. Growth/survival curves were developed in raw gray water and sterile inoculated crude gray water. A strain of Escherichia coli isolated from crude gray water was used, and it was used for inoculation in sterile crude gray water and sterile crude gray water supplemented with phosphorus, nitrogen and glucose. The curves were plotted with correlation between the time (hours) and the number of viable cells. Regarding the influence of nutrients on the growth/survival of Escherichia coli in sterile crude gray water we have that the phosphorus supplementation at the concentrations tested did not make a significant difference in the growth of the bacteria analyzed. On the other hand, when sterile crude gray water was supplemented with different concentrations of nitrogen, a difference in growth/survival of Escherichia coli was observed. The glucose supplementation sample showed higher Escherichia coli population growth, even dextrose not being a more appropriate source for glucose supplementation, but this increase demonstrates the enormous capacity of Escherichia coli to absorb carbon from the environment in which it is found.